Pendidikan Era Globalisasi Di Indonesia - Bakhrudin All Habsy; Dina Dwi Febriani; Mus Shafira Ramadhani Yapono; Nabiila Az Zahra Yuliandhika (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Education in the era of globlization is an education system that is developing in the midst of rapid global change, marked by advancesin technology, information and communication that influence almost all aspects of life. Current developments, especially in the current era of globalization, demand high quality human resources. To obtain quality human resources, good education is needed. In the learning process, appropriate strategies need to be implemented to facilitate the achievement of educational goals in the era of globalization. This research uses qualitative methods, with a type of literature or library study method that uses review methods using journal sources, articles and other scientific works that are relevant to the object of study in this research. The results of this research include (1) Discovery Learning (2) Inquiry Learning (3) Inductive Learning (4) Hybrid Learning (5) Communication and Information Technology Based Learning (6) Culture Based Learning.